Lyapunov functionals and practical stability for stochastic differential delay equations with general decay rate - Caraballo Tomas (Electronic journal of qualitative theory of differential equations, 2022)
This paper stands for the almost sure practical stability of nonlinear stochastic differential delay equations (SDDEs) with a general decay rate. We establish some sufficient conditions based upon the construction of appropriate Lyapunov functionals. Furthermore, we provide some numerical examples to validate the effectiveness of the abstract results of this paper.